Studying Teachers' Degree of Classroom Implementation, Teachers' Implementation Practices, and Students' Learning as Outcomes of K-12 STEM Professional Development - Lin, Peiyi (ProQuest LLC, 2013)
With a growing demand for an enhanced K-12 education for strengthening students' conceptual learning, interest, and career awareness in science, technology, engineering, and mathematics, teacher professional development projects have been viewed as an efficient approach. However, a variety of external and teacher factors may prevent such projects from achieving their expected impact. The purpose of this study was to investigate the effects of external and teacher factors in BUILD IT, a K-12 STEM professional development training project. The study analyzed the degree of classroom implementation of 71 high- and middle-school teachers. Forty-seven teachers completely implemented the training and their implementation practices were analyzed, as were their 396 students' learning outcomes. Both qualitative and quantitative analyses were used. The correlation of each external and teacher factor with each outcome was conducted first, followed by a final multi-factor analysis to investigate the factors as a group. Findings revealed: (1) The school's socioeconomic status, class size, principal's support, and the students' science ability was related to teachers' degree of classroom implementation; (2) Type of administrative support, the teachers' former STEM work experience, and the students' science ability were correlated with the teachers' implementation practices; (3) The school's socioeconomic status, match of subject taught and professional development, years of teaching, and the teachers' educational backgrounds were associated with the middle-school students' conceptual understanding; (4) The students' prior skill level in science was correlated with their conceptual understanding; (5) The students' BUILD IT experience seemed to contribute to an increase in their career interest, while the use of process-based design logs and project portfolios boosted their post-project outcomes. The findings have implications for school leaders and policy makers. School leaders can: (1) Minimize negative external factors by prioritizing instruction; (2) Promote teachers' implementation by assuming a more active role; (3) Improve teachers' professional knowledge and skills by encouraging teachers' sharing of professional learning. Bottom-up professional development models might also accomplish these goals. In addition, policies on professional development should require a close alignment between training and subject areas. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]